Capital flight to Germany: Two alternative measures. (April 2020) - Cheung, Yin-Wong; Steinkamp, Sven; Westermann, Frank
Highlights: Two measures of capital flight to Germany are refined and analyzed empirically. Trade misinvoicing is adjusted for time and country-specific trade costs. TARGET2 balances are adjusted for official flows and current account transactions. Crisis variables (flight-to-safety) and currency misalignment are driving factors. Traditional determinants such as covered interest differentials play a limited role. Abstract: We use two measures to study two capital flight channels for Germany. One measure is based on the concept of trade misinvoicing and one on net claims and liabilities in the Eurosystem of central banks. For both measures, we propose refinements to enhance the assessment of capital flight. We find that capital flight towards Germany via these two channels has been quite sizable in the recent decade and can tally to about 2% of GDP annually. Regarding their determinants, we show that the two capital flight measures are driven by both common and measure-specific factors. Traditional determinants such as covered interest differentials only play a limited role, while crisis-specific factors such as economic policy uncertainty, the ECB collateral policy, as well as currency misalignment are driving factors of the investors' apparent flight-to-safety behavior.